Analgesic effect of Photobiomodulation Therapy: An in vitro and in vivo study. Issue 10 (9th July 2019) - Zupin, Luisa; Ottaviani, Giulia; Rupel, Katia; Biasotto, Matteo; Zacchigna, Serena; Crovella, Sergio; Celsi, Fulvio
Abstract: Laser therapy, also known as Photobiomodulation (PBM) is indicated to reduce pain associated with different pathologies and applied using protocols that vary in wavelength, irradiance and fluence. Its mechanisms of action are still unclear and possibly able to directly impact on pain transmission, reducing nociceptor response. In our study, we examined the effect of two specific laser wavelengths, 800 and 970 nm, extensively applied in the clinical context and known to exert important analgesic effects. Our results point to mitochondria as the primary target of laser light in isolated dorsal root ganglion (DRG) neurons, reducing adenosine triphosphate content and increasing reactive oxygen species levels. Specifically, the 800 nm laser wavelength induced mitochondrial dysregulation, that is, increased superoxide generation and mitochondrial membrane potential. When DRG neurons were firstly illuminated by the different laser protocols and then stimulated with the natural transient receptor potential cation channel subfamily V member 1 (TRPV1) ligand capsaicin, only the 970 nm wavelength reduced the calcium response, in both amplitude and frequency. Consistent results were obtained in vivo in mice, by subcutaneous injection of capsaicin. Our findings demonstrate that the effect of PBM depends on the wavelength used, with 800 nm light mainly acting on mitochondrial metabolism and 970 nm light on nociceptive signal transmission. Abstract : Photobiomodulation effects in vivo and in vitro models were evaluated, aiming to elucidate analgesic effect of laser light. Both wavelengths induce mitochondrial dysfunction, but only one (970 nm) provokes a reduction in Ca 2+ influx mediated by transient receptor potential cation channel subfamily V member 1 (TRPV1) and a stronger analgesic effect on capsaicin‐treated mice. These results can be useful for optimizing laser protocols for analgesia in clinical practice.